c.1 - Nagaraj, R. (New Delhi, 2006)
R Nagaraj, a development economist well-known for his research and analytical writings on industrial development, economic growth and reforms in India, has compiled the present volume, offering readers some of his important writings on the subject. Studies included in this volume, carried out over a decade, represent an effort to grapple with a few contemporary issues of economic growth, industrial change and policy initiatives in India. These studies are motivated by the desire to carefully examine some of the widely held propositions on the aggregate and sectoral economic performance, premises of a few reform measures and the outcome of some aspects of the economic reforms initiated in the 1990s. A crisp Introduction by the author provides a brief background to these studies, situates them in the relevant literature and indicates how they contributed to the ongoing discourse on economic analysis and policy. The two abiding concerns in these studies are to examine the quality of statistics employed as they could have a bearing on research findings and their interpretation, and to provide analyses of a relatively long period to eschew hasty inferences from limited observations. ""Aspects of India's Economic Growth and Reforms"" promises to be a valuable reference for all concerned - students, economists and policymakers alike.
Keywords: Macroeconomic performance